Experience Rate of Elbow Pain and Morphological Abnormality of Humeral Medial Epicondyle among Youth Baseball Players - Kotoura, Yoshihiro (Orthop J Sports Med, 2016)
OBJECTIVES: The aim of this study was to investigate the experience rate of elbow pain and to clarify the relationship between morphological abnormality of the humeral medial epicondyle and positions among baseball players in elementary school (ES), junior high school (JHS) and high school (HS). METHODS: In this study, 4353 baseball players who participated in our medical screening (2008-2015) were enrolled. There were 1545 players from ES, 1934 players from JHS, and 874 players from HS. We asked them to answer the questionnaire to investigate the experience of elbow pain, and the position they played. Ultrasonography of the humeral medial epicondyle was examined and irregularity, fragmentation, and malunion of the humeral medial epicondyle. The results were analyzed statistically. P < 0.05 was considered significant for all statistical analyses. RESULTS: The experience rates of elbow pain among players in ES, JHS, and HS were 26.0%, 27.0%, and 68.3%. The rates of abnormality of humeral medial epicondyle among players in ES, JHS, and HS were 18.2%, 36.3%, and 39.9% (Table 1). The experience rate of elbow pain among pitchers and catchers was significantly higher than the fielders in ES (Table 2), however, there were no significant differences between positions in JHS and HS (Table 3,4). According to the rate of morphological abnormalities of humeral medial epicondyle, pitchers and catchers were significantly higher than fielders in ES, while only pitchers were significantly higher than the fielders in JHS and HS (Table 2,3,4). CONCLUSION: The experience rate of elbow pain among baseball players rose as the age increased, and the rate in HS was almost 70%. The rates of morphological abnormality of humeral medial epicondyle among pitchers and catchers were high and the tendency was observed from a young age. The primary prevention of elbow injuries in youth baseball players of all ages should be considered.